The The Bioceanic Route as a field of produced discourses - Andrade Asato, Thiago (2021)
This article is part of the product of a thesis entitled “The Bioceanic Route as a field of possibilities for the development of tourist activity”. It focuses on the possibility of opening an Integration Route between South American countries aimed at development in its different interfaces in the respective countries that make up the so-called Bioceanic Corridor, namely: Brazil, Paraguay, Argentina and Chile. The designation of "Integration Route" gives more legitimacy, even in the literal sense of the word "integration", opening up more possibilities for development, interconnecting other cities that will benefit in an inductive way, making the development of Mato Grosso do Sul more uniform. This route that crosses the Bioceanic Route and, consequently, the Bioceanic Road Corridor can provide opportunities for a change of local perspective, mainly due to the investments made in infrastructure of all kinds in the border area comprising Porto Murtinho and Carmelo Peralta, valuing the collective interest of the local communities. Theoretical sources establish a confluence of disciplinary fields as knowledge from the field of knowledge on Discourse Analysis is discussed from different approaches, contextualizing the paths necessary to define the analytical categories that were selected for the analysis of perceptions chosen.